Opinions towards physical activity interventions using Facebook or text messaging: Focus group interviews with vocational school‐aged adolescents. (6th November 2018) - Van Dyck, Delfien; D'Haese, Sara; Plaete, Jolien; De Bourdeaudhuij, Ilse; Deforche, Benedicte; Cardon, Greet
Abstract: Feasible and effective interventions to promote physical activity among vocational school‐aged adolescents are strongly needed. Text messaging and Facebook are feasible and acceptable delivery modes for PA interventions among youth. However, little is known about the opinion of vocational school‐aged adolescents regarding behavioural change techniques that can be applied through Facebook or text messaging. Therefore, our aim was to gain insight into the opinions of vocational school‐aged adolescents towards the use of different behaviour change techniques and towards Facebook/text messaging as a delivery mode for PA interventions. Six focus groups were conducted with 41 adolescents from the first grade (12–14 years) of secondary vocational schools in Flanders (Belgium). In total 41 adolescents participated and completed a questionnaire about their text messaging and Facebook use prior to group discussions. Focus group discussions were audio‐recorded and analysed using a thematic analysis method in Nvivo. Participants thought that different behaviour change techniques (e.g., providing feedback, goal setting, self‐monitoring, social comparison) could be integrated in a PA intervention using text messaging and Facebook and were enthusiastic about participating in such an intervention. They indicated that text messages are an easy way to receive information about PA, and that a group page on Facebook is ideal to share information with others. Participants deemed it very important that the group page on Facebook would only include peers with whom they also share an offline connection. Furthermore, adolescents stressed the importance of having autonomy (e.g., to determine their personal activity goals, to self‐monitor their behaviour) and of being active together with friends. This qualitative study revealed that the use of Facebook and text messaging is promising as a delivery method for PA interventions among vocational school‐aged adolescents. The adolescents were keen to participate in an intervention that integrates behaviour change techniques using text messaging or Facebook.